The Queen Elizabeth Way: Public Utility Versus Public Space - van Nostrand, John (Urban History Review / Revue d'histoire urbaine, 1983)
This paper provides an informal history of the Queen Elizabeth Way — Canada's first 'superhighway" and one of the earliest controlled-access roads in North America. It traces this history from the 1930s, the period of original design and construction to the present day. Throughout, the author examines not only the changing perception of the highway held by its designers and users, but also, its role as a key element in the development of the "Golden Horseshoe," one of the most heavily populated regions of North America. Most importantly, this paper explores the demise of the Queen Elizabeth Way as a combined traffic-artery-cum-regional-public-space and its transformation into a utilitarian object. It concludes by speculating that one of the key lessons to be learned from this experience is the need, in future highway design, to redirect our efforts to strike a more effective balance between these two roles.